2-(4,5-Dimethoxy-2-nitrophenyl)-4-methoxy-3-methyl-9-phenylsulfonyl-9H-carbazole - P. Narayanan; K. Sethusankar; Velu Saravanan; Arasambattu K. Mohanakrishnan (Acta Crystallographica Section E, 2014)
In the title compound, C28H24N2O7S, the carbazole system is essentially planar, with a maximum deviation of 0.0644 (19) Å for the C atom connected to the 4,5-dimethoxy-2-nitrophenyl group. The dihedral angle between the carbazole moiety and the dimethoxy-substituted nitrophenyl ring is 58.55 (7)°. The sulfonyl group forms two intramolecular C—H...O bonds with the adjacent carbazole system, forming two cyclic S(6) motifs. In the crystal, molecules are linked along the a axis in bands consisting of cyclic R33(15) motifs through two further C—H...O hydrogen bonds.